Rancang Bangun Oven Pengering Lidi Sawit Dengan Sistem Double Blower - Roni Novison; Fajar Akhriadha (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2023)
The process of drying palm sticks carried out by umkm in Kampar Regency, precisely in the Terentang mine, still needs to be solved in the drying process, which only has sunlight and changes in hot weather in the quality drying palm sticks. Therefore, an oven is designed to improve the quality of drying palm sticks using a double blower system and a branched pipe. This oven is manufactured for an open iron drying room measuring 3x3 cm with volume dimensions of 100 cm3, then for the heating room using a hollow iron measuring 3x3 cm with dimensions of length 50 cm, width 50 cm, and height 50 cm. Heat flow pipe using a pipe of 2 inches along the 800 mm and connected using a branched pipe 50 mm long with a pipe size of 1 inch as much as 4 sections that lead to each rack in the oven chamber. Based on the calculation of the design capacity of this palm stick drying oven, the total capacity of this oven is 28.8 kg on each shelf. However, from experiments that have been carried out with the drying process of palm sticks at full capacity, it is measuring the water content of each shelf is uneven. The bars on each frame and the rods in the middle pile do not experience differences in air content because the hot air obtained is less when compared to the top bundle of posts and the bars at the bottom.